USERS PERCEPTION OF A WIND TOWER FOR PASSIVE COOLING IN HOT DRY AREA OF SOUTHERN ALGERIA: A CASE OF OULED DJELLAL BISKRA - Torkia, A; Mazouz, S; Djouima, A (university of el oued/جامعة الوادي, 2018)
This paper is a synopsis of the results of a socio-cultural research on the wind tower as a sustainable cooling system, introduced in hot dry areas of southern Algeria. This element is integrated into 80 dwellings neighbourhood in Ouled Djellal. The wind towers were closed or removed by users despite their proven thermal performance by the authors [1]. This paper reveals the causes behind this rejection and users’ perception issues using in situ observation, interviews and survey. It unveiled that wind towers are useful, successful and are to be incorporated into new residential buildings’ designs only if incompatibility errors between design, implementation, use, and control system are avoided. The survey proved, the cultural acceptance of this new element in Algeria by the population surveyed of low to medium social class (56.82% yes and yes under conditions, of which 38.64% yes without conditions).
Article
Keywords: Wind tower, perceptions, passive cooling, hot and semi-arid climate, sphinxplus2